2014
DOI: 10.1007/s12035-014-9005-1
|View full text |Cite
|
Sign up to set email alerts
|

Location- and Subunit-Specific NMDA Receptors Determine the Developmental Sevoflurane Neurotoxicity Through ERK1/2 Signaling

Abstract: It is well established that developmental exposure of sevoflurane (an inhalational anesthetic) is capable of inducing neuronal apoptosis and subsequent learning and memory disorders. Synaptic NMDA receptors activity plays an essential role in cell survival, while the extra-synaptic NMDA receptors activation is usually associated with cell death. However, whether synaptic or extra-synaptic NMDA receptors mediate developmental sevoflurane neurotoxicity is largely unknown. Here, we show that developmental sevoflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 62 publications
(70 reference statements)
1
27
0
Order By: Relevance
“…The activation of ERK1/2 is necessary for signal transduction, from cell membrane surface receptors to nucleus. ERK1/2 MAPK signaling pathway has been reported to play essential roles in developmental neuronal survival and sevoflurane neurotoxicity (68), to increase dendritic spine density during synaptogenesis in hippocampal neurons, and to help improving learning and memory abilities (37,38). MEK (ERK1/2 kinase) inhibitor PD98059 is specific for ERK1/2 pathway, by noncompetitively binding to MEK, it is commonly used to block ERK1/2 pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation of ERK1/2 is necessary for signal transduction, from cell membrane surface receptors to nucleus. ERK1/2 MAPK signaling pathway has been reported to play essential roles in developmental neuronal survival and sevoflurane neurotoxicity (68), to increase dendritic spine density during synaptogenesis in hippocampal neurons, and to help improving learning and memory abilities (37,38). MEK (ERK1/2 kinase) inhibitor PD98059 is specific for ERK1/2 pathway, by noncompetitively binding to MEK, it is commonly used to block ERK1/2 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Recent researches have demonstrated that ERK1/2 plays positive roles in neuroprotective processes. Sevoflurane neurotoxicity in immature brain is related to ERK1/2 signaling pathway and apoptosis related factors such as Caspase-3, B-cell lymphoma/leukemia-2 (Bcl-2) and Bcl-2 associated X (Bax) (68). It would be interesting to know whether LBP effects on sevoflurane-injured neurons through ERK1/2 pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Upregulation of phosphorylated ERK1/2 (p-ERK1/2) upon NMDA stimulation promotes neuronal survival, whereas downregulation of p-ERK1/2 leads to severe neurodegeneration[ 16 , 17 ]. Sevoflurane has been reported to inhibit the phosphorylation of extracellular signal-regulated kinase 1 and 2 (ERK1/2) in the hippocampal tissues [ 18 ]. Due to the critical role of NMDA receptors and its downstream signaling molecules in learning and memory processes[ 19 ], these receptors may play a role in sevoflurane-induced cognition change in brain.…”
Section: Introductionmentioning
confidence: 99%
“…Sevo urane is an inhalational anesthetics, which is commonly used in cesarean delivery and pediatric clinical application [2]. Previous evidence has suggested that sevo urane exposure has certain harm on learning and cognitive functions, especially for children [5,11]. In the current study, the P7 rats were recruited for animal experiments to investigate the role of sevo urane in developing brain.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely used in cesarean delivery and pediatric clinical application [2]. Sevo urane has some neurotoxicity for the nervous system, especially for developing brain [3][4][5]. The animal experiments have proved that volatile anesthetics at clinical concentrations can lead to neuronal apoptosis and impair the learning ability and cognitive function in neonatal and aged rodents [6][7][8].…”
Section: Introductionmentioning
confidence: 99%